Environmental Pollution Biomarker: Fish Antioxidant Défense System Alterations - Dr.Dev Brat Mishra (Genius Journals, 2022)
Heavy metals (Fe, Zn, Cu, Mn and Cd) pollution in River Nile's Rosetta Branch has been studied in this work to determine the influence on the antioxidant defence system and lipid peroxidation indicator MDA levels in O. niloticus tissues (liver and white muscles). High levels of agricultural drainage water, sewage, and industrial waste water flow into the Rosetta Branch of the Nile, which has a negative impact on the living creatures, particularly fish. Water and fish samples from stations II and III showed an increase in the content of heavy metals (Fe; Zn; Cu; Mn; Cd) over the winter months. The accumulation patterns of heavy metals in the muscles of O. niloticus were as follows: Fe > Zn > Mn > Cu and Cd. During the winter months, the bioaccumulation factor (BAF) was greater than during the summer months. Oxidative enzymes (SOD, CAT, GPx, GST, and GR) as well as MDA levels in the liver and white muscles of O. niloticus (stations II and III, particularly in winter) exhibited a considerable rise. White muscles had lower activity of antioxidant enzymes and greater amounts of MDA
Keywords: Heavy metals; pollution; antioxidant defense system